High capacity synergistic immobilization of simulated trivalent actinides by zirconia/zircon multiphase ceramics. Issue 2 (15th January 2023) - Xiong, Yingwei; Li, Jiajing; Zhao, Dandan; Dan, Hui; Ding, Yi
Abstract: Zircon (ZrSiO4 ) ceramics are candidate waste form for immobilizing actinides. However, ZrSiO4 with single phase suffers from the low actinides solubility. Herein, 0.2Zr1- a Nd a O2- a /2 /Zr1- b Nd b SiO4- b /2 (0≤ a + b  ≤ 0.3) multiphase ceramics were fabricated and their actinides immobilization ability and aqueous stability were evaluated. The evolutions of phase and microstructure affected by Nd doping were investigated. 0.2Zr1- a Nd a O2- a /2 /Zr1- b Nd b SiO4- b /2 ceramics with 0≤ a + b ˂0.1 exhibited monoclinic ZrO2, tetragonal ZrO2 and ZrSiO4 mixed phases, while monoclinic ZrO2, tetragonal ZrO2, ZrSiO4 and Nd2 Si2 O7 phases with 0.1≤ a + b  ≤ 0.3. The increase of lattice volume revealed the successful lattice immobilization of Nd by ZrO2 /ZrSiO4 . Due to synergistic immobilization effect, the Nd immobilization capacity of ZrO2 /ZrSiO4 is up to 10 at%, which is higher than that of single-phase ZrSiO4 (4 at%). Furthermore, the obtained ceramics waste form exhibited good compactness and excellent aqueous stability. The results indicated that zirconia/zircon multiphase ceramics can be a potential candidate waste form for actinides.